2017
DOI: 10.1002/jrs.5305
|View full text |Cite
|
Sign up to set email alerts
|

Raman microspectroscopy of blue‐green historical beads: Comparative study of undamaged and strongly degraded samples

Abstract: Confocal Raman microspectroscopy is used to substantially supplement existing experimental data on historical blue‐green beads with respect to the presence and distribution of potassium antimony silicate (KSS) crystals. Problem of degradation of blue‐green beads on historical artifacts accounts for topicality of the work. The reasons for possible short‐term (several years) degradation of beads and the presence of neighboring damaged and undamaged beads on a single item remain unknown in spite of multiple exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…This result agrees well with the Raman spectroscopy data. The appearance of an intense line of Raman scattering peaked at 980 cm −1 [17], usually associated with the Si 2 -O 6 4 (Q 2 ) units, in the degraded turquoise bead glass evidences in support of the simplification of the glass structure in the course of its degradation and dominance of the silicate chain (Q 2 ) units in damaged glass.…”
Section: Micro-ftir Spectroscopymentioning
confidence: 85%
See 1 more Smart Citation
“…This result agrees well with the Raman spectroscopy data. The appearance of an intense line of Raman scattering peaked at 980 cm −1 [17], usually associated with the Si 2 -O 6 4 (Q 2 ) units, in the degraded turquoise bead glass evidences in support of the simplification of the glass structure in the course of its degradation and dominance of the silicate chain (Q 2 ) units in damaged glass.…”
Section: Micro-ftir Spectroscopymentioning
confidence: 85%
“…Recently, we have presented our Raman study of the 19th century turquoise beads at different stages of degradation and demonstrated substantial changes of the glass structure at the late stages of corrosion, as well as its changes depending on depth in subsurface layers of a degraded glass grain [17]. Besides, we have determined for the first time the characteristic Raman bands of orthorhombic KSS [14,17]. 5 This paper presents the results of the Fourier-transform infrared (FTIR) spectroscopy study of historical turquoise glass beads.…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectra of the synthesized standard of orthorhombic KSbOSiO 4 are presented in Refs. [25,38,39]. Their characteristic feature is an intense narrow peak at about 532 cm −1 .…”
Section: Synthesis and Analysis Of Ksbosiomentioning
confidence: 99%
“…Balakhnina and co‐workers used Raman microspectroscopy to compare undamaged and strongly degraded samples of blue‐green historical beads with respect to the presence and distribution of potassium antimony silicate crystals. Their results can be used for the optimization of storage conditions and restoration procedures for historical items . Peris‐Diaz et al employed Raman spectroscopy coupled to chemometrics to the discriminate provenance and geological age of amber.…”
Section: Art and Archaeologymentioning
confidence: 99%